2020
DOI: 10.3390/nu12051356
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Age-Related Changes in the Brain of the Zucker Lepr fa/fa Rats

Abstract: Metabolic syndrome (MetS) is an association between obesity, dyslipidemia, hyperglycemia, hypertension, and insulin resistance. A relationship between MetS and vascular dementia was hypothesized. The purpose of this work is to investigate brain microanatomy alterations in obese Zucker rats (OZRs), as a model of MetS, compared to their counterparts lean Zucker rats (LZRs). 12-, 16-, and 20-weeks-old male OZRs and LZRs were studied. General physiological parameters and blood values were measured. Immunochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 67 publications
1
36
0
1
Order By: Relevance
“…As well as in the DIO model, we have previously reported in OZRs blood-brain barrier (BBB) alterations, neuronal loss, and gliosis both in the frontal cortex and in the hippocampus [13]. The behavioral tests revealed cognitive alterations in older OZRs as well as in DIO rats [12,14].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…As well as in the DIO model, we have previously reported in OZRs blood-brain barrier (BBB) alterations, neuronal loss, and gliosis both in the frontal cortex and in the hippocampus [13]. The behavioral tests revealed cognitive alterations in older OZRs as well as in DIO rats [12,14].…”
Section: Introductionmentioning
confidence: 87%
“…Although there are numerous data regarding the metabolic alterations in obese conditions and the development of neuroinflammation [8,9,12,14,31], no mechanism has been presented concerning obesity-related cholinergic and synaptic impairments in the brain. Therefore, this study was designed to investigate whether the memory and learning impairments in older OZRs [14] were also related to cerebral cholinergic and synaptic alterations, specifically identifying the markers that were implicated. The investigation was carried out in brain areas, in which cholinergic neurotransmission is widely represented: the frontal cortex, especially the motor region, and the hippocampus, which is involved in learning and memory tasks [14].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the PFC has anatomical connections with feeding-related areas, including the lateral hypothalamus, NAc shell and limbic reward sites [ 153 , 154 ]. The PFC circuitry is linked with cognitive aspects of searching for food [ 155 ], self-control, salience attribution and awareness [ 156 ], reward-based decision-making [ 66 ], and a dysregulation of such circuit might lead to the development of obesity [ 157 , 158 , 159 , 160 ]. In keeping with this latter observation, different imaging studies suggested the PFC activation in response to food-related cues [ 161 , 162 , 163 ]; such activation is also implicated in yohimbine-induced reinstatement of food seeking in rodents [ 164 , 165 ].…”
Section: Drd4 and Feeding Behaviormentioning
confidence: 99%
“…The hyperproliferation and in ltration of these pro-in ammatory mediators and high metabolic demand of the brain predisposes it to oxidative stress, which exacerbates the neuroin ammation (Camandola and Mattson, 2017). Oxidative stress-induced neuroin ammation alters neurotrophic factors levels, disrupts neurotransmission balance, and contributes to neuronal damage and cognitive de cit (Tangvarasittichai, 2015;Chen et al, 2019;Tomassoni et al, 2020). Moreover, dysregulation of lipids, such as triacylglycerol and cholesterol correlates positively with neurodegenerative diseases (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene Supresses Palmitic acid-induced Neurooxidoin ammation via Attenuation of Oxidative stress and NF-κB-p65 activation in Female Rats Introduction Neuro-in ammation (arising from meta-in ammation) describes an immuno-metabolic disorder of the nervous system, arising from derangements of the metabolic and in ammatory pathways in response to various cues including infection, autoimmunity, nutrients, or toxic metabolites (Tomassoni et al, 2020). Nutrients (such as free fatty acids) may accumulate in the nervous tissue such as the microglia due to excessive positive energy balance.…”
mentioning
confidence: 99%